2015
DOI: 10.5296/jse.v5i4.8588
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles, Parental Involvement in School, and Educational Functioning of Children with Special Needs Integrated into Mainstream Education

Abstract: The study examined the relationship between parenting style and parental involvement in school and educational functioning among children with various disabilities integrated into mainstream education. It includes 116 parents of children with special needs who reported their children according to formal educational evaluations they possessed. The sample of children reported by parents disproportionately represents six age layers | =9.23, SD=1.85|and 3 main disability groups. Multivariate regression analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(49 reference statements)
0
2
0
1
Order By: Relevance
“…They set clear rules for the child and work to enforce them, but also recognise the child's personal desires and opinions. Most studies have found authoritative parenting style to be positively associated with adaptive functioning and mental health (Keller, 2012) and negatively associated with anxiety disorders, social anxiety (Yaffe, 2015), depressive symptomology (Dwairy et al, 2006) and EDs (Latzer et al, 2015), more so than the other two parenting styles.…”
Section: Parenting Patterns Associated With Edsmentioning
confidence: 99%
See 1 more Smart Citation
“…They set clear rules for the child and work to enforce them, but also recognise the child's personal desires and opinions. Most studies have found authoritative parenting style to be positively associated with adaptive functioning and mental health (Keller, 2012) and negatively associated with anxiety disorders, social anxiety (Yaffe, 2015), depressive symptomology (Dwairy et al, 2006) and EDs (Latzer et al, 2015), more so than the other two parenting styles.…”
Section: Parenting Patterns Associated With Edsmentioning
confidence: 99%
“…Taken together, studies suggest that permissive and authoritarian parenting styles are related to non-adaptive functioning and lower mental health (Keller, 2012), as well as to social anxiety (Yaffe, 2015), depression and EDs (Latzer et al, 2015). Furthermore, social anxiety and depression were found to be associated both with risk of EDs (Herpertz et al, 2011) and with parenting styles (Yaffe, 2015).…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…Family communication is creating, sharing and managing meaning in interactions between family members as a continuous, complex communication process, changing activities from the past to the reality of family members to the future (Chris Segrin, 2011). Implementing appropriate parenting styles in raising children with special needs will have a real positive impact on the child's functioning at the emotional, social and educational levels (Yaffe, 2015). In general, among children with multi-problem developmental disabilities (Downs syndrome and autism), this parenting style is expressed in high levels of responsiveness, sensitivity and training, and it is associated with improved communicative and social functioning (Dyches et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Salah satu sikap andil orang tua pada anak tunanetra yaitu keputusan orang tua menyekolahkan anak tunanetra di sekolah khusus yaitu SLB Negeri Sragen. Yaffe (2015) melakukan penelitian terkait gaya pengasuhan dan keterlibatan orang tua anak berkebutuhan khusus di sekolah. Peranan orang tua penting bagi perkembangan anak, terutama di bidang akademik.…”
Section: Pendahuluanunclassified